Are Level 3 fair values reflected in firm value? Evidence from European banks - Katja Kisseleva; Daniela Lorenz (European School of Management and Technology (ESMT), 2016)
This paper investigates whether, and if so, to what extent, Level 3 fair values disclosed by European banks provide useful information to investors and are reflected in firm value changes. Using a unique sample of 416 hand-collected firm-year observations from European banks reporting under IFRS, in contrast to previous research conducted in the US, we find no overall evidence that changes in Level 3 fair values are associated with changes in firm value. However, the value relevance of Level 3 fair values depends on the category assigned to financial instruments. Level 3 fair values that are held for trading are reflected in firm value. Further analyses suggest that this effect is driven predominantly by banks that operate in market-based economies and hire audit firms with deep industry expertise.
Keywords: M41; N20; 650; Fair value; financial instruments; value relevance; banks